Gentleman bandit : [large type] the true story of Black Bart, the old West's most infamous stagecoach robber - Boessenecker, John, 1953- (Thorndike Press large print nonfiction series., 2023)
"Black Bart is regarded not only the most notorious stage robber of the Old West but also the best behaved. Over his lifetime, Black Bart held up at least twenty-nine stagecoaches with mild, polite commands. Such behavior earned him the title of a true "gentleman bandit," and his ultimate fate remains one of the greatest mysteries of the Old West. Now John Boessenecker sheds new light on Black Bart, bringing to life the story of the mysterious stage robber who doubled as a rich, genteel socialite in the golden era of the Wild West"--